CFD simulation of two phase segmented flow in microchannel reactor using volume of fluid model for biodiesel production - Mohd Laziz, A. (Springer Verlag, 2017)
One of the advantages of using microchannel reactor in chemical process is enhancement of mass and energy transfer due to the high area-to-volume ratio created by the multiphase droplet. This total interfacial area can be varied by controlling the size of the droplet based on different volumetric flow ratio between continuous and disperse phase. CFD method is used to estimate the size of the droplet using VOF model. In many cases, there is always balance between simulation result accuracy and computational cost. In this study, the grid sensitivity analysis is investigated to see the result accuracy at different meshing quality. From this multiphase simulation, it was found that the simulation is highly dependent on grid size. The droplet size cases showing deviation ±5 and ±20 for highest and lowest meshing quality respectively, which the lowest meshing quality must have at least one layer of mesh refinement at the wall. By knowing this, one can have confidence on using lowest meshing quality for a lower computational cost but still at an acceptable level of result accuracy. © Springer Nature Singapore Pte Ltd. 2017.